4
$\begingroup$

Trying to reinvent the spirit of Calculus, I was trying to Understand the Leibniz Rule of Differentiation under Integration sign. To check my understanding, I was considering this integral: $$ I(b) = \int^1_0 \frac{x \log(b + x)}{1 + x^2} dx $$ After some simplification, I came upon the Integral in question: $$ 2I(1) = \frac{1}{4} \log^2{2} + \frac{\pi^2}{16} + 2\int^1_0\frac{b \log b}{1 + b^2} db $$

Now I am a bit confused about how to progress. Maxima shows the answer to be $-\frac{\pi^2}{48}$.

This is not a homework problem.

$\endgroup$
1
$\begingroup$

$$ \begin{align} \int_0^1\frac{x\log(x)}{1+x^2}\,\mathrm{d}x &=\sum_{k=0}^\infty\int_0^1(-1)^kx^{2k+1}\log(x)\,\mathrm{d}x\tag1\\ &=\sum_{k=0}^\infty\frac{(-1)^{k+1}}{(2k+2)^2}\tag2\\ &=\frac14\sum_{k=1}^\infty\frac{(-1)^k}{k^2}\tag3\\ &=-\frac14\left(\sum_{k=1}^\infty\frac1{k^2}-2\sum_{k=1}^\infty\frac1{(2k)^2}\right)\tag4\\ &=-\frac{\pi^2}{48}\tag5 \end{align} $$ Explanation:
$(1)$: expand $\frac{x}{1+x^2}$ into a geometric series
$(2)$: integrate by parts: $u=\log(x)$, $\mathrm{d}v=x^{2k+1}\,\mathrm{d}x$
$(3)$: substitute $k\mapsto k-1$
$(4)$: an alternating sum is all the terms minus twice the even terms
$(5)$: $\zeta(2)=\frac{\pi^2}6$

$\endgroup$
  • $\begingroup$ The fourth line seems particularly tricky to me. But the derivation is concise enough. $\endgroup$ – sarker306 Mar 1 '18 at 11:48
  • $\begingroup$ @sarker306: I've added some explanation to hopefully clarify the steps. $\endgroup$ – robjohn Mar 1 '18 at 15:21
  • $\begingroup$ @sarker306: I could have skipped step $(4)$ and just used $\eta(2)=\frac{\pi^2}{12}$, where $\eta$ is the Dirichlet Eta Function. $\endgroup$ – robjohn Mar 1 '18 at 15:26
  • $\begingroup$ Thank you. This solution is worth revisiting. $\endgroup$ – sarker306 Mar 1 '18 at 16:08
  • $\begingroup$ after getting myself familiar with using infinite series (expansions of elementary functions), this solution looks like the easiest one to apply. $\endgroup$ – sarker306 Jul 10 at 7:43
2
$\begingroup$

This calculation may contains some convergence problem, but it'll be resolved easily.

Using integration by parts, we have $$ I(0)=\int_{0}^{1}\frac{x\log x}{1+x^{2}}dx = \left[\frac{1}{2}\log(1+x^{2})\log x\right]_{0}^{1} - \int_{0}^{1} \frac{1}{2}\log(1+x^{2})\frac{dx}{x} $$ Since $$ \lim_{x\to 0} \log(1+x^{2})\log x = \lim_{x\to 0} \frac{\log(1+x^{2})}{x^{2}}\cdot x\cdot x\log x = 0, $$ we have $$ I(0) = -\frac{1}{2}\int_{0}^{1} \frac{\log(1+x^{2})}{x}dx. $$ Now use substitution $x^{2} = t$, then $$ I(0) = -\frac{1}{4} \int_{0}^{1}\frac{\log(1+t)}{t}dt $$ Now use the Taylor series of $\log(1+t)$, $$ I(0) = -\frac{1}{4} \int_{0}^{1} \frac{1}{t}\left(t-\frac{t^{2}}{2}+\frac{t^{3}}{3}-\cdots\right)dt = -\frac{1}{4}\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{n^{2}} = -\frac{1}{4}\left(\sum_{n=1}^{\infty}\frac{1}{n^{2}}-2\sum_{n=1}^{\infty} \frac{1}{(2n)^{2}}\right) = -\frac{1}{4}\cdot \frac{1}{2}\zeta(2) = -\frac{\pi^{2}}{48}. $$

$\endgroup$
1
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} \int_{0}^{1}{x\ln\pars{x} \over 1 + x^{2}}\,\dd x & \,\,\,\stackrel{x\ \to\ x^{\large 1/2}}{=}\,\,\, {1 \over 4}\int_{0}^{1}{\ln\pars{x} \over 1 + x}\,\dd x \,\,\,\stackrel{x\ \to\ -x}{=}\,\,\, -\,{1 \over 4}\int_{0}^{-1}{\ln\pars{-x} \over 1 - x}\,\dd x \\[5mm] & \stackrel{\mrm{IBP}}{=}\,\,\, {1 \over 4}\int_{0}^{-1}{-\ln\pars{1 - x} \over x}\,\dd x = {1 \over 4}\int_{0}^{-1}\mrm{Li}_{2}'\pars{x}\,\dd x = {1 \over 4}\,\mrm{Li}_{2}\pars{-1} \\[5mm] & = {1 \over 4}\,\sum_{n = 1}^{\infty}{\pars{-1}^{n} \over n^{2}} = {1 \over 4}\,\sum_{n = 1}^{\infty}\braces{% {1 \over \pars{2n}^{2}} - \bracks{{1 \over n^{2}} - {1 \over \pars{2n}^{2}}}} \\[5mm] & = -\,{1 \over 8}\ \underbrace{\sum_{n = 1}^{\infty}{1 \over n^{2}}} _{\ds{\pi^{2} \over 6}}\ =\ \bbx{-\,{\pi^{2} \over 48}} \end{align}

$\endgroup$
  • $\begingroup$ You don't need series if your purpose is to use $\zeta(1)=\frac{\pi^2}{6}$. Change of variable tool is enough. $\endgroup$ – FDP Mar 1 '18 at 22:33
  • $\begingroup$ @FDP $\zeta\left(\color{#f00}{2}\right) = \pi^{2}/6$. I was late. So, I was trying to build something different. Sorry for the $overkill$ !!!. $\endgroup$ – Felix Marin Mar 1 '18 at 22:43
  • $\begingroup$ You are right, my mistake ! It's weird for me to use integral definition of dilog and use series for $\zeta(2)$ in the same computation. $\endgroup$ – FDP Mar 1 '18 at 22:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.